If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x(3x + 2) = 5x(5x + -2) Reorder the terms: 7x(2 + 3x) = 5x(5x + -2) (2 * 7x + 3x * 7x) = 5x(5x + -2) (14x + 21x2) = 5x(5x + -2) Reorder the terms: 14x + 21x2 = 5x(-2 + 5x) 14x + 21x2 = (-2 * 5x + 5x * 5x) 14x + 21x2 = (-10x + 25x2) Solving 14x + 21x2 = -10x + 25x2 Solving for variable 'x'. Reorder the terms: 14x + 10x + 21x2 + -25x2 = -10x + 25x2 + 10x + -25x2 Combine like terms: 14x + 10x = 24x 24x + 21x2 + -25x2 = -10x + 25x2 + 10x + -25x2 Combine like terms: 21x2 + -25x2 = -4x2 24x + -4x2 = -10x + 25x2 + 10x + -25x2 Reorder the terms: 24x + -4x2 = -10x + 10x + 25x2 + -25x2 Combine like terms: -10x + 10x = 0 24x + -4x2 = 0 + 25x2 + -25x2 24x + -4x2 = 25x2 + -25x2 Combine like terms: 25x2 + -25x2 = 0 24x + -4x2 = 0 Factor out the Greatest Common Factor (GCF), '4x'. 4x(6 + -1x) = 0 Ignore the factor 4.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {0, 6}
| 8-x-2x=-10 | | -2=4x-3x-9 | | 16=4x+7x-6 | | 16=4x+x | | x+1.6x=1 | | x+9-5x=-23 | | -.22x^2+30x-210=0 | | -4x+6+6x=20 | | 6-x+2x=-3 | | x*12=-36 | | -13y=169 | | -27=-3x-6x+9 | | 5=-5x+6x-1 | | 7x+9+3x=-81 | | 72x+15=24 | | -21=5x+3x+1 | | s+m=hform | | -12t-52=-16 | | a+7=4a-14 | | 4y-6=y+12 | | 5y-2(4k+5)= | | -8=-4+2x+8 | | Y=mx+nx^2 | | 20=2x+2x+8 | | -6+7x-5x=-8 | | 3+8=12-6+5 | | -.17x^2+22x-295=0 | | 22-18x=x-8 | | factor-.17x^2+22x-295=0 | | 2x+6-6x=38 | | 4(2x-3)(5x+2)=64 | | 3y-6+5y-9= |